Efficacy of Noninvasive 1060-nm Diode Laser for Medial Knee Fat Reduction - Chadakan Yan (2022)
Introduction: Laser lipolysis is a rapidly growing noninvasive body-contouring treatment in Asians. There is increasing demand for leg contouring, especially in areas where unwanted fat deposits are prominent despite diet and exercise. Medial fat knees are one of the esthetic concerns of women today and can be a challenging problem in terms of treatment. There are few noninvasive options to remove fat from these areas. This study aims to evaluate the safety and efficacy of a 1060-nm diode laser for medial knee fat reduction. Methods: Nineteen subjects with localized unwanted fat on the medial knees were enrolled into this study. All of them were treated with a single session of 1060-nm diode laser at a power setting of 1.0–1.4 W/cm2, depending on patient tolerance. Body weight, knee circumference at 3 cm above the medial epicondyle of the femur, and knee fat thickness measured by ultrasonography were recorded at baseline and 1, 3, and 6 months after treatment. Clinical photographs and ultrasound images were taken before and after treatment. Side effects were documented during follow-up visits. Subjects answered a satisfaction questionnaire at the completion of the study. Results: All subjects were female, with mean age of 32.3 ± 5.3 years and body weight of 59.8 ± 11.6 kg. The average power setting was 1.3 ± 0.1 W/cm2 with pain score of 6.1 ± 1.0. Significant reduction in knee circumferences (p < 0.001) at 1-, 3-, and 6-month follow-up visits compared with baseline, and knee fat thickness measured by ultrasound in both axial and sagittal plane at 1 and 6 months after treatment (p = 0.036 and p < 0.001, respectively) were recorded. Side effects were mild and transient, including mild erythema and tenderness. Conclusion: The 1060-nm diode laser is effective and safe for knee circumference and medial knee fat layer thickness reduction. Trial registration: ClinicalTrials.gov identifier, TCTR20220219002. Retrospectively registered on February 19, 2022.